Report of Caridina babaulti Bouvier, 1918 (Crustacea: Decapoda: Caridea: Atyidae) and description of a new species Caridina kutchi sp. nov. from Gujarat, India - Pandya, Pranav J.; Richard, Jasmine (Zootaxa, 2019)
This study aims to report the freshwater shrimps of the genus Caridina H. Milne Edwards, 1837, from the Indian state of Gujarat, which has a unique landscape and climatic conditions that form a significant environment for biological studies. Caridina babaulti Bouvier, 1918, is re-described with type specimens and fresh collections from Shetrunji River, Saurashtra Peninsula. Caridina kutchi sp. nov., is described from Khari River, Kutch Peninsula.